FEATURES OF THE POETICS OF THE CHRONOTOPE (Scientific journal of the Fergana State University, 2023)
The article analyzes the literary and functional features of the chronotope, one of the current problems of literary criticism. The chronotope serves to describe the relationship between the world and man, fully experience the depths of the hero‘s emotional experiences, express the writer's literary and ideological purpose, and reveal the content and form of the work. It highlights the distinctive features of the creative style and reflects the national way of thinking. The chronotope reinforces the internal consistency of the work, forming a genre and a plot. The category of time and space fulfills a generalizing function.